Prihodnost temeljnih pravic v Evropski uniji - Kogovšek Šalamon, Neža (Delavci in delodajalci, 2015)
Freedom of movement is one of the fundamental freedoms of the EU law and one of the most important rights arising from EU citizenship. The most important reasons for moving into another EU Member State are employment and work, while the most important question for an EU citizenship that intends to move together with their family members is who is considered to be a family member according to the law of the host state. In case of rainbow families the answer to this question is far from simple.
Keywords: človekove pravice; družina; Evropska unija; istospolna partnerska skupnost; otroci; pravna ureditev; starši; svoboda gibanja